2019
DOI: 10.1155/2019/6018432
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Hypertension and a Commonly Inherited IGF1R Variant (rs2016347) Reduce Breast Cancer Risk by Enhancing Mammary Gland Involution

Abstract: Background Terminal duct lobular units (TDLUs) are the anatomic sites of breast cancer initiation, and breast tissue involution resulting in lower TDLU counts has been associated with decreased breast cancer risk. The insulin-like growth factor (IGF) pathway plays a role in breast involution, and systemic changes in this developmental pathway occur with hypertensive disorders of pregnancy (HDP), which have also been associated with lower breast cancer risk, especially in women carrying a functional variant of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Turner et al ( 51 ) reported that IGF1R expression is increased in resected breast cancer tumor tissues and is associated with early recurrence. Powell et al ( 52 ) demonstrated that the commonly inherited IGF1R variant (rs2016347) reduces breast cancer risk by enhancing mammary gland involution. In addition, triptolide and IGF1R inhibitor (AG1024) can synergistically inhibit the proliferation and induce the apoptosis of triple-negative breast cancer cells ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Turner et al ( 51 ) reported that IGF1R expression is increased in resected breast cancer tumor tissues and is associated with early recurrence. Powell et al ( 52 ) demonstrated that the commonly inherited IGF1R variant (rs2016347) reduces breast cancer risk by enhancing mammary gland involution. In addition, triptolide and IGF1R inhibitor (AG1024) can synergistically inhibit the proliferation and induce the apoptosis of triple-negative breast cancer cells ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…This histologic analysis confirmed that no sample contained preneoplastic or neoplastic cells. Furthermore, terminal duct lobular unit (TDLU) counts were independently and blindly determined on each H&E slide as recently reported [ 7 ]. For adipocyte cross-sectional area assessment, four representative images from each H&E slide were analyzed at × 50 magnification (measuring ≥ 50 adipocytes per image) using Fiji imaging software with the open-source Adiposoft v1.13 plugin, as previously described [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, elevated serum levels or increased expression of IGF-1 has been implicated in the development of various non-breast cancers [ 31 – 35 ]. Of mechanistic relevance to the present study, the normal breast tissue of women with a history of preeclampsia who also inherit the lower expressing T allele of IGF1R rs2016347 exhibits increased mammary gland involution, a histologic predictor of reduced breast cancer risk [ 36 ].…”
Section: Introductionmentioning
confidence: 99%